Choice of Needle in Spinal Anesthesia among Anesthesiologists in Teaching Hospitals of Sindh - Madiha Raza, Furkan Hyder, Noor-us-Saba, Hasan Ali Shah, Adeel Hussain, Syed Farjad Sultan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine frequency of anesthesiologists practicing pencil- point spinal needles in teaching hospitals of Sindh, Pakistan. Study design: Cross-sectional study. Place and Duration of Study: The Indus Hospital, Aga Khan University Hospital Karachi, Liaquat National Hospital Karachi, Civil Hospital Karachi, Jinnah Postgraduate Medical Centre (JPMC) Karachi, Sindh institute of Urology & Transplantation (SIUT) Karachi, Abbasi Shaheed Hospital Karachi, Ziauddin Hospital Karachi, PNS Shifa Hospital Karachi, Civil Hospital Hyderabad, Chandka Medical College Larkana and Peoples Medical College Nawabshah from 1stJune 2018 to 30thApril 2019. Methodology: Sixty FCPS anesthesiologists or equivalent working in teaching hospitals of Sindh for more than one year, either gender and age 30-70 years were enrolled in the study. MCPS specialists were excluded. Results: Majority anesthesiologists were males 48 (80%). The median working experience was 15 years (IQR): (10-21) with no significant difference between both the genders (mean: 17.2 vs 13.8, p=0.277). Thirty three (55.5%) had professional experience of ≥15 years. Approximately 42% belonged to Aga Khan University hospital. All participants had work experience of general surgery, while 54(90%) worked in Urology, 53(88.3%) participants had experience of Orthopedics, Gynecology and Obstetrics. Conclusion: Although majority of consultants use 25G Pencil Point Needles for spinal anesthesia but still we need to educate more practitioner of government institutes to use smaller gauge spinal needles and the reason of using smaller gauge pencil point needles should be to prevent the chances of PDPH.